2010
DOI: 10.4102/sajpsychiatry.v16i1.209
|View full text |Cite
|
Sign up to set email alerts
|

Audit of child and adolescent psychiatry in a teaching hospital in Nigeria: Prevalence, pattern and implication for improved services

Abstract: Child and adolescent psychiatry in developed countries is characterised by a well-organised and co-ordinated mix of service delivery facilities such as hospital, residential and day treatment units run by a multidisciplinary complement of professionals including psychiatrists, psychologists, counsellors and social workers.1-4 Systematic development efforts have created a surveillance system that includes parents, educational, judicial and medical institutions, and mental health professionals.By routine or inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…In this study, the age group with the lowest prevalence of mental health disorders were those who were 10 years and below. Other researchers [35,43] have similar findings. It is also possible that some in this lower age group, may have been presenting to the Paediatric Clinic where some may have been lost during referral to the child and adolescent mental health clinic, while others may have actually received evaluation, hence the need for stronger collaboration.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In this study, the age group with the lowest prevalence of mental health disorders were those who were 10 years and below. Other researchers [35,43] have similar findings. It is also possible that some in this lower age group, may have been presenting to the Paediatric Clinic where some may have been lost during referral to the child and adolescent mental health clinic, while others may have actually received evaluation, hence the need for stronger collaboration.…”
Section: Discussionsupporting
confidence: 74%
“…The developed world realizing the importance of sound mental health in the development of children and adolescents, organized several school-based mental health interventions geared towards mental health promotion or primary prevention for all students in school [35]. Available researches have shown moderate to strong evidence that these interventions are effective in promoting good mental health and related outcomes among school children [36].…”
Section: Introductionmentioning
confidence: 99%
“…However, contradicting findings are reported in other parts of the world. In Nigeria, (50%) of the referrals to a tertiary academic center had schizophrenia, (15%) had delirium, and 9% had seizure disorders [7]. Nevertheless, they mentioned that the proportion of mood and psychotic disorders to other diagnoses increased in time along with the changes in diagnostic and classification systems and promotion in professionals' knowledge and attitude toward childhood psychiatric problems.…”
Section: Discussionmentioning
confidence: 99%
“…Another American study in eight psychiatric hospitals reported that mood disorders were more common than other disorders among children and adolescents (38%) [6]. In a Nigerian tertiary aca-demic psychiatric hospital, 50% of the referrals suffered from schizophrenia [7]. In a group of inpatients in Taiwan, the first three common diagnoses were depressive disorder (50%), Bipolar Disorder (BD) (14.3%), and schizophrenia (14.3%) [8].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence rate is remarkably higher in Europe, North America and Australia where one-sixth to half of patients with early onset psychosis were estimated to have substance use disorders [42][43][44][45][46][47][48][49]. In Nigeria, whereas substance use has been shown to be prevalent among adolescents in the general population [50][51], substance use disorders tend to be under-represented in child and adolescent psychiatric clinic samples [27,52]. The low rates of substance use disorder in our study sample may be attributed to a number of factors including under-detection due to non-disclosure, the younger age of the sample and nonavailability of in-patient substance use treatment program within the study location.…”
Section: Discussionmentioning
confidence: 99%